Optimizing MSME Development in Marketing Management to Increase Production Efficiency at 99 Juice Shop in Telang - Lailatul Istiqomah; Neli Lintang Happy Daily; Mashudi (Managing: Jurnal Bisnis dan Manajemen, 2026)
This study discusses efforts to optimize the development of micro, small, and medium-sized businesses, particularly in the area of ​​marketing strategy management to maximize the production effectiveness of Kedai Jus 99, located in the Telang area, Bangkalan, Madura. By applying a qualitative methodology based on case studies, the study successfully uncovered several fundamental obstacles that hinder the growth of this business, including limited marketing area, inefficient production processes, and a lack of product innovation that has resulted in declining profits. Based on direct observations with the involvement of researchers, it was revealed that the marketing pattern implemented still relies on traditional methods such as word of mouth and the installation of signage, not exploiting the potential of digital technology-based marketing. As a concrete solution, this study proposes the development of a digital-based marketing system that includes utilizing social networks, establishing partnerships with online food delivery service providers, and establishing a pre-order mechanism to improve raw material planning. The implementation of this series of strategies is predicted to be able to expand market share and increase the productivity of Kedai Jus 99 as a micro-economic actor in the beverage sector.